Microbial, Chemical, and Radial Pollution of Freshwater in Iraq - Hameda K. Zghair (World Journal of Experimental Biosciences, 2020)
Water pollution in Iraq is a complex and multifaceted problem that encompasses various types of pollution, including microbial pollution, chemical pollution, and radiation pollution. These forms of contamination pose significant threats to the environment, public health, and the overall well-being of the Iraqi population. In this comprehensive article, we will explore the causes, consequences, and mitigation efforts related to microbial, chemical, and radiation pollution of water in Iraq.
Keywords: Chemical pollution, Freshwater, Iraq, Microbes, Radial pollution